Harmonic analysis of dynamic hysteresis response of BaTiO3 bulk ceramics - K. Kanchiang (2018)
In this work, the dynamic ferroelectric hysteresis properties in response to dynamic electric field of BaTiO3bulk ceramics was investigated using the harmonic analysis approach. Fourier transformation was used to analyze the periodic polarization signal on frequency domain via each discrete harmonic. From the results, the hysteresis area is found to depend only on the first harmonic of the real part. On the other hand, the remnant polarization depends on all odd harmonics of the real part. Further, the coercive field can be found from the phase-lag between the inverse Fourier signals re-calculated from the first harmonic of the real part and that of the imaginary part. The hysteresis properties from the harmonic analysis match well with those of the original measurement. This suggests that the harmonic analysis is one of the powerful techniques which can be used to predict hysteresis behavior. © Taylor & Francis Group, LLC.